Potential of Intercropping of Oil Palm (E. guineensis Jacq.) and Liberica Coffee (C. liberica L.): A Case Study in Smallholder Plantation - Erick Firmansyah; Arif Umami (Journal of Applied Agricultural Science and Technology, 2021)
Oil palm (Elaeis guineensis Jacq.) has become the main plantation commodity in Indonesia. Climate change phenomena and competitiveness fluctuation of palm oil commodities have led to increased need for optimized land productivity while maintaining sustainability. This research aimed to study the potential of oil palm intercropping with liberica coffee (Coffea liberica L.) in several smallholder oil palm plantations in Riau Province, Sumatera Island, Indonesia. Measurements in the middle of the non-harvesting path of oil palm showed the age of oil palm is directly proportional to the difference between air and soil temperature and relative humidity under canopy. Oil palm roots were dominantly distributed vertically in solum 0 - 30 cm and always dominant compared to coffee at all horizontal distances observed. While the dominant root coffee distribution was in solum 31 - 60 cm. Analysis results show the tap roots extend no further than 30-45 cm below the soil surface. It was known that oil palm roots are dominantly distributed at a distance of 2-3 m from the trunk while the coffee roots are dominantly distributed at a distance of 1-2 m from the trunk. Analysis of oil palm yields in the intercropping system showed no significant decrease compared to monocropping systems with relatively the same age and production input. Coffee production per tree has decreased by 25-30% compared to the average production in monocropping systems.